MEKANISME PENDAFTARAN HAJI SECARA ONLINE MELALUIMOBILE BANKING BANK MUAMALAT KCP PROBOLINGGO - Hanifatul Hasanah, Uum; Kholifah, Kholifah (universitas Islam Zainul Hasan Genggong, 2024)
This research aims to overcome the Hajj data collection mechanism for prospective Hajj pilgrims by digitizing Hajj registration via the Muamalat Digital Islamic Network (DIN) mobile banking application. The stages for registering for Hajj through Muamalat DIN are as follows: First, prospective pilgrims first open an account online at Muamalat DIN. Second, register and make an initial deposit of IDR 25 million into the Hajj Pilgrimage Savings Account (RTJH). After making the payment, the congregation will receive proof of payment and a validation number. Third, the congregation enters the validation number into the Ministry of Religion's Smart Haji application to get the portion number and year of departure. The results of this research show that it uses a descriptive-qualitative type of research and approach. creating a Hajj information system. The research method used is by providing online Hajj and Umrah services. The results can be concluded that the Hajj information system is more efficient and accurate than the previous Hajj registration system which was still done manually. Registration for the Haj portion can now be done online via Muamalat DIN without having to come to a branch office. Bank Muamalat has also synchronized with the Smart Hajj application belonging to the Ministry of Religion of the Republic of Indonesia so that registration for paying off Hajj costs can be done online. As a Bank Recipient of Deposits for Hajj Organizing Costs (BPS BPIH), we have carried out digital innovation in the form of registering and paying off Hajj costs online. On line. This makes it easier for prospective Hajj pilgrims because it is practical, easy, anytime and anywhere right from their hand.